2019
DOI: 10.1186/s13058-019-1160-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of TGFBI confers resistance to trastuzumab in human breast cancer

Abstract: Background Acquired resistance to trastuzumab is a major clinical problem in the treatment of HER2-positive (HER2+) breast cancer patients. The selection of trastuzumab-resistant patients is a great challenge of precision oncology. The aim of this study was to identify novel epigenetic biomarkers associated to trastuzumab resistance in HER2+ BC patients. Methods We performed a genome-wide DNA methylation (450K array) and a transcriptomic analysis (RNA-Seq) comparing tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 59 publications
(72 reference statements)
0
34
0
Order By: Relevance
“…Moreover, it has been reported that TGFBI might be associated with Lapatinib resistance in HER2-positive breast cancer cell lines [253]. On the other hand, epigenetic silencing of TGFBI by DNA methylation has been found to contribute to the trastuzumab resistance in HER2-positive cell models [254]. Taken together, TGFBI can function as a chemo-sensitizer or a risk of chemo-resistance in various cancers.…”
Section: Transforming Growth Factor B Induced (Tgfbi) Protein and Brmentioning
confidence: 98%
“…Moreover, it has been reported that TGFBI might be associated with Lapatinib resistance in HER2-positive breast cancer cell lines [253]. On the other hand, epigenetic silencing of TGFBI by DNA methylation has been found to contribute to the trastuzumab resistance in HER2-positive cell models [254]. Taken together, TGFBI can function as a chemo-sensitizer or a risk of chemo-resistance in various cancers.…”
Section: Transforming Growth Factor B Induced (Tgfbi) Protein and Brmentioning
confidence: 98%
“…TGFBI was also identi ed to be a hub gene strongly associated with oral squamous cell carcinoma and to be able to promote tumor metastasis [43] . In addition, the epigenetic silencing of TGFBI by DNA methylation can confer resistance to trastuzumab in breast cancer [44] . Furthermore, Wang et al [45] found the aberrant expression of TGFBI in RC.…”
Section: Discussionmentioning
confidence: 99%
“…Palomeras et al reported that primary breast tumors that developed trastuzumab resistance present a loss of expression of transforming growth factor beta-induced protein (TGFBI) by hypermethylation. TGFBI inhibits the HER2 receptor and AKT (124). Abnormal activation of PI3K/AKT is common in breast cancer.…”
Section: Regulation Of the Pi3k/pten/akt/mtor Signaling Pathway By Dnmentioning
confidence: 99%